(untitled) (The Review of Diabetic Studies, 2024)
Uncontrolled traumatic hemorrhage and the resultant acute coagulopathy remain the leading causes of preventable death in severely injured patients. Conventional coagulation tests (CCTs), such such as Prothrombin Time (PT) and Activated Partial Thromboplastin Time (aPTT), suffer from significant operational and mechanistic limitations in the acute trauma setting, particularly their inability to assess dynamic clot formation, platelet function, and fibrinolysis in real time. Viscoelastic Hemostatic Assays (VHAs), principally Thromboelastography (TEG) and Rotational Thromboelastometry (ROTEM), have emerged as essential Point-of-Care (POCT) diagnostics. These whole-blood tests provide rapid, comprehensive profiles of clot initiation, strength, and stability, allowing for the functional characterization of Trauma-Induced Coagulopathy (TIC). This review provides laboratory specialists and technicians with an in-depth guide to VHA methodology, focusing on analytical quality assurance, detailed parameter interpretation, and the integration of VHAs into goal-directed Massive Transfusion Protocols (MTPs). Despite heterogeneity across next-generation platforms and ongoing clinical debate regarding overall mortality benefit (as demonstrated by trials such as ITACTIC), VHAs consistently accelerate time to diagnosis, facilitate targeted component and concentrate therapy, and demonstrably reduce unnecessary blood product exposure. Successful implementation requires rigorous quality management, strict pre-analytical control, and institutional commitment to device-specific, evidence-based transfusion algorithms.